1987
DOI: 10.1002/pd.1970070708
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of 45,X/46,XY mosaicism in a fetus with asymmetric gonadal dysgenesis

Abstract: An 18 week abortus had been prenatally diagnosed as a 45,X/46,XY mosaic. The fetus was a phenotypic male with glandular hypospadias, a horseshoe kidney and asymmetric gonadal dysgenesis. This case represents a rare instance of prenatally diagnosed 45,X/46,XY mosaicism with an abnormal phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…There have been two other reports of a similar sex chromosome mosaicism in the fctus that went undetected at amniocentesis. In one, the amniocentesis result was 46,XY and the near-normal male infant had a 45,X/46,XY karyotype (Ladda, 1977). The other case showed only 45,X cells at amniocentesis, but the aborted phenotypically normal female fetus had a mosaic karyotype 45,X/46,X,Ynf (Nocera et al, 1985).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There have been two other reports of a similar sex chromosome mosaicism in the fctus that went undetected at amniocentesis. In one, the amniocentesis result was 46,XY and the near-normal male infant had a 45,X/46,XY karyotype (Ladda, 1977). The other case showed only 45,X cells at amniocentesis, but the aborted phenotypically normal female fetus had a mosaic karyotype 45,X/46,X,Ynf (Nocera et al, 1985).…”
Section: Discussionmentioning
confidence: 93%
“…The phenotype of postnatally ascertained cases of 45,X/46,XY mosaicism varies from normal female through Turner syndrome and varying degrees of virilization to normal male. However, in the more than 50 cases of prenatally diagnosed 45,X/ 46,XY mosaicism that have been reported (Kirkilionis et al, 1987;Wheeler et al, 1988;Hsu, 1989), the phenotype is overwhelmingly normal or near-normal male. It hais therefore been recommended that careful ultrasound of the uro-genital system be carried out when 45,X/46,XY mosaicism is detected prenatally.…”
Section: Discussionmentioning
confidence: 99%
“…The association between Y"' and 45,X/46,XYnf has been noted since 1971 (Caspersson et u/., 1971). Further cytogenetic studies indicated that the Y nf is in fact a pseudo-dicentric chromosome with duplication of Yp and euchromatic Yq sequences, and with a loss of Yq heterochromatin (Magenis and Donlon, 1982;Wisniewski and Hirschhorn, 1982;Magenis et al, 1985;Ganshirt-Ahlert et al, 1987). The dicentric nature of the Ynf chromosome possibly predisposes it for anaphase lag or mitotic non-disjunction resulting in mosaicism.…”
Section: Discussionmentioning
confidence: 99%
“…A further North American survey (Hsu, 1986) and recent ongoing data collection (Hsu, unpublished data) brought the number of45,X/46,XY mosaicism cases to 47. With the addition of seven recently published cases (Kirkilionis et al, 1987, Wheeler et al, 1988, a total of 54 cases was reviewed. The diagnosis of chromosome mosaicism was based on the findings of both cell lines (45,X and 46,XY) in a minimum of two independently cultured vessels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation